Perlindungan Hukum Terhadap Hak Guru Honorer Yang Tidak Terpenuhi Pada Guru Di Sekolah Swasta - Syasti, Bunga Saphira; Raharja, Brian Kerta; Julyetha, Sophie Azdha; Adiwijaya, Khosyiko Noer; Saputra, Dimas Nanda (Neolectura, 2024)
This research focuses on the legal protection for honorary teachers whose rights are not fulfilled in private schools. Honorary teachers, often employed on a non-permanent basis, are vulnerable to not receiving their entitled rights, such as salaries, social security, and other benefits. Despite their significant role in the education system, particularly in private institutions, the lack of legal protection often leads to exploitation and adverse working conditions. The aim of this study is to examine the legal framework governing the rights of honorary teachers in Indonesia, with a specific focus on private schools. It explores the extent to which these teachers are protected under Indonesian labor laws and educational regulations, particularly the Education Law and the Labor Law. This study also investigates the challenges honorary teachers face in asserting their rights and the mechanisms available for them to seek redress. Using a qualitative approach, the research analyzes case studies, legal documents, and interviews with both teachers and school administrators to understand the situation. The findings highlight gaps in the enforcement of legal protections, with many teachers unaware of their rights or too vulnerable to challenge non-compliance. This study concludes that honorary teachers in private schools require stronger legal protections to ensure their rights are fulfilled. Recommendations include improved awareness programs for both teachers and administrators, the strengthening of legal frameworks, and better enforcement mechanisms to prevent the exploitation of these educators. Legal reform and policy adjustments are necessary to provide honorary teachers with adequate protection, promoting fair and just working conditions in the education sector.